2016
DOI: 10.1002/cctc.201501049
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Scaling Relations for Chemisorption Energies on Transition‐Metal‐Exchanged Zeolites ZSM‐22 and ZSM‐5

Abstract: Copper exchange on all the different T sites of ZSM‐22 and ZSM‐5 is considered and the chemisorption energies of dioxygen, OH, and O species are studied. We show that for different T sites the adsorption energies vary significantly. The oxygen adsorption energy on copper‐exchanged zeolites is quite similar to those of the most selective catalysts for oxidation reactions, that is, Ag and Au surfaces. The chemisorption energies of oxygen, carbon‐, and nitrogen‐containing species on different transition metals ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 80 publications
0
19
2
Order By: Relevance
“…On the other hand, metal atoms at double vacancies are found to adsorb *OOH in a monodentate mode, but they allow adsorbates to interact with support plane due to the less protrusion of metal atom (Table S2). Similar behavior has been observed on transition metal exchanged zeolites with cage‐like rings …”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, metal atoms at double vacancies are found to adsorb *OOH in a monodentate mode, but they allow adsorbates to interact with support plane due to the less protrusion of metal atom (Table S2). Similar behavior has been observed on transition metal exchanged zeolites with cage‐like rings …”
Section: Resultsmentioning
confidence: 99%
“…5,[36][37] Since the late 90's (first with small clusters, then with periodic models), DFT based calculations were brought to determine copper active site structures in metal cation-exchanged zeolites, and recently for copper-exchanged chabazite. 4,[16][17]23,34,[38][39][40][41][42][43][44][45][46][47][48][49][50][51] A large set of studies concluded (or assumed) the better stability of Cu II located at the 6MR, with respect to 8MR, in the absence of adsorbates. 34,[42][43][44] X-ray absorption spectroscopy (XAS) is ideally suited to study transition metal based catalysts under realistic or operating conditions (gas composition, temperature, pressure etc.)…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18][19] This originates from the presence of a distribution of active sites, 21,22,28 which leads to a larger complexity in predicting macroscopically measurable observables.…”
Section: Introductionmentioning
confidence: 99%